Prevalence of goitre and its associated factors in a coastal district of Karnataka - Kamath, Veena G; Jacob, George P; Agrawal, Ayushi; Kamath, Asha; Shenoy, Revathi P (Indian Journal of Community Health, 2015)
Context: Iodine deficiency Disorders (IDDs) are a major public health problem globally. In India more than 200 million are at risk for this disorder. It affects people of all ages and both sexes. The mental impairment caused by IDD especially in children is an important consequence of IDD. Aim: To find the prevalence of IDDs and the associated factors with it. Settings and Design: A school based cross – sectional study. Methods and Material: The study was done in Udupi district of Karnataka using a pretested, semistructured questionnaire. The villages of the three talukas (Udupi, Kundapur and Karkala) of Udupi district were sampled according to Probability Proportionate to Size (PPS).One school was chosen for the study from each of the 30 selected villages. Minimum of 90 students were selected from each school. Salt and urine samples were collected for Iodine estimation from a sub sample. Goitre was graded according to WHO/UNICEF/ICCIDD criteria. Results: A total of 3023 children were examined (M = 49.1%, F = 50.9%). The prevalence of goitre in Udupi district was 19.8%. The prevalence of goitre was found to be more amongst females compared to males (p = 0.021) and also was found to be increasing with the increasing age (p = 0.003). Of the 539 salt samples analyzed 23.7 % were inadequately iodized. Education of the father, fish consumption and occupation of the mother were found to be significant predictors of goitre. Conclusions: Goitre is a public health problem in Udupi district of Karnataka. The adequately Iodized salt coverage which should have been more than 90 % is not fulfilled. More awareness is required amongst the people about IDDs and its predictors.